Automated three-component synthesis of a library of γ-lactams - Fenster, Erik; Hill, David; Reiser, Oliver; Aubé, Jeffrey (Beilstein Journal of Organic Chemistry, 2012)
A three-component method for the synthesis of γ-lactams from commercially available maleimides, aldehydes, and amines was adapted to parallel library synthesis. Improvements to the chemistry over previous efforts include the optimization of the method to a one-pot process, the management of by-products and excess reagents, the development of an automated parallel sequence, and the adaption of the method to permit the preparation of enantiomerically enriched products. These efforts culminated in the preparation of a library of 169 γ-lactams.
Keywords: γ-lactam; maleimide; organocatalysis; parallel synthesis; reductive amination